Seasonal pattern of glycosylation in frog liver. Issue 1 (February 1991) - Leoni, S.; D'Alessandro, A.; Conti, R.; Marino, M.; Spagnuolo, S.; Mangiantini, M. T.
Abstract : The circannual behaviour of glycosylation and protein synthesis in frog liver slices was studied following the incorporation of 3 H-galactose and 14 C-glucosamine into glycolipids and glycoproteins and 3 H-leucine into proteins. The activity of two enzymes the galactosyl-transferase and the N-acetyl-glucosaminyl-1-P-transferase was determined. The incorporations of both sugars into the soluble fraction and into the lipid extract present a maximum during the spring-summer period. The incorporation into the protein fraction displays a different pattern: 14 C-Glucosamine and 3 H-leucine incorporation increases from winter to a maximum in autumn; the incorporation of 3 H-Galactose has a sharp peak during spring. The pattern of glycosyltransferase activities is similar to the pattern of incorporation of the two saccharides into proteins, indicating these enzymes as important control points for glycosylation in Anurae.